Helping computers help themselves. - Pescovitz, D. (IEEE spectrum)
At IBM and elsewhere, researchers are developing the components and feedback loops necessary for computer systems to run themselves. The hope is that the constant and costly intervention of database and network administrators trying to figure out what must be done will soon be a thing of the past. Among the first of these projects are some that enable computer systems to optimize computing resources and data storage on their own.